Comparison of the training load during high-intensity interval resisted training programmed by different exercise duration - Sengoku, Y.; Tsunokawa, T.; Kobayashi, K.; Tsubakimoto, S. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Training for competitive swimmers is characterised by its high volume swimming mileage, compared to other individual sport events. However, several studies investigated whether this high volume training is actually necessary for high performance achievement compared to high intensity training (Faude et al. 2008; Sperlich et al. 2010). These results suggested that high intensity (low volume) training could also enhance endurance capacity and race performance by the same amount as the traditional high volume (low intensity) training. Therefore, new training program introducing high intensity workouts is a matter of concern nowadays. An epoch-making training procedure of High Intensity Interval Training (HilT) had been introduced by Tabata et al. (1996), a training regimen of 20 sec exercise at 170%V02max intensity with 10 sec interval repeated by 8 sets, so-called 'Tabata Protocol'. This training protocol was suggested to enhance not only maximal accumulated oxygen deficit (anaerobic capacity) but also V02max (aerobic capacity). Furthermore, Ogita et al. (2010) reported an even shorter training set, 5 sec supra-maximal swim with 10 sec rest repeated by 5 sets, which indicated to have a potential to increase V0 2max as well as the glycolytic system. Even with these clear evidences of the HilT to enhance the swimmer's physiological capacity, it is hard to introduce this concept to the actual training field, because these training effects have been tested in swimming flume condition. To realise the HilT in actual training situation we attempt to combine HilT with a traditional Sprint Resisted Training, which is a common training method for sprint training utilising elastic rubber tube (Maglischo 2003). The purpose of this study was to investigate and compare the training load during this new High Intensity Interval Resisted Training (HIIRT) programed by different exercise duration.